Anthropometric predictors for cardiovascular risk in Indigenous women in Mexico: an inexpensive alternative in rural clinical practice - María del Guzmán Márquez; Ivonne Vizcarra-Bordi; TERESA RIVERA; Alejandra Benitez-Arciniega (James Cook University, 2021)
Introduction: Cardiovascular diseases are one of the leading causes of death in Mexico. Although the use of anthropometric indicators facilitates the diagnosis of cardiovascular risk (CVR), their use is limited in rural communities with limited resources. This article evaluated and demonstrated predictive capacity of three anthropometric indexes for CVR in Indigenous women in Mexico from Matlatzinca ethnic group. Methods: A cross-sectional study of 93 Indigenous women was carried out. CVR was calculated with the Framingham risk score and used as the reference method by comparing it with waist circumference (WC), conicity index (CoI) and waist-height index (WHI). Receiver operating characteristic (ROC) curves were used to analyze the area under the curve (AUC), sensitivity and specificity for each anthropometric index. Results: Cut-off points (and AUC) for each anthropometric index were WHI 0.63 (0.763), CoI 1.29 (0.756) and WC 91 (0.663). Conclusion: In this population, WHI presented the greatest discrimination power; it was considered the best predictor of CVR because of its high sensitivity. It was demonstrated that the anthropometric indexes WC, CoI and WHI could be used in clinical practice in rural areas without sufficient resources for serological tests.